Sustainable Entrepreneurship Utopian Idea or a New Business Model for the 21st Century? - Sołoducho-Pelc, Letycja (Contemporary organisation and management. Challenges and trends, 2020)
Entrepreneurial activities are seen as important to business, society, environment. The purpose of this paper is to give an up-to-date assessment of the key topics discussed in the literature on sustainable entrepreneurship. It has become a more accessible, and essential, topic in academic literature and practice. Nowadays, enterprises are required to reconcile contradictions arising at the interface between: business – society and business – environment. Sustainable entrepreneurship is a new area of research that combines the concept of sustainable development and entrepreneurship. This is due to the rapid increase in the environmental problems that affect the whole world. Sustainable entrepreneurship is about discovering, creating, and using entrepreneurial opportunities that contribute to sustainable development by generating social and environmental benefits for society. The article presents the background, achievements, and current trends in sustainable entrepreneurship. The vast majority of research results in the field of sustainable entrepreneurship are of a conceptual nature. One should also be aware of the overly optimistic approach to the idea of sustainable entrepreneurship as a panacea for social and environmental problems of the modern world. Nevertheless, this concept has the potential to mobilize social and environmental activities. The practice of sustainable entrepreneurship is poorly understood. Further research in this area is necessary to move from the mere concept of an ideal enterprise to the practical implementation of sustainable entrepreneurship. As this paper is a literature review, a systematic literature review is conducted to assess new contributions to the field, based on which the role of sustainable entrepreneurship in the XXI century, research directions and the criticism of sustainable entrepreneurship are identified and discussed. This literature review of research on sustainable entrepreneurship may develop an agenda for future research paths and practice.